2014
DOI: 10.1371/journal.pone.0091661
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-424 Is Down-Regulated in Hepatocellular Carcinoma and Suppresses Cell Migration and Invasion through c-Myb

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related mortality worldwide. MicroRNAs (miRNAs) are important regulators of multiple cellular processes, and the aberrant miRNAs expressions have been observed in different types of cancer including HCC. Their pathysiologic role and their relevance to tumorigenesis are still largely unknown. In this study, we demonstrated the down-regulation of miR-424 in HCC cell lines and tissues by quantitative RT-PCR analyses. Overexpression of miR-424 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 41 publications
5
63
1
Order By: Relevance
“…For example, miR-191, an oncogenic miRNA, was shown to be highly expressed in HCC and involved in cell proliferation, apoptosis and epithelial mesenchymal transition in HCC, and its hypomethylation has been proved to be associated with poor prognosis [32], interestingly, here we found miR-191 could be down-regulated by baicalein; miR-222-5p and miR-675 were reported to be up-regulated in HCC tumor tissues and positively associated with recurrence after resection [33], whereas our result showed that they were both down-regulated under baicalein treatment; miR-424-3p has been demonstrated to be down-regulated in HCC and suppresses tumor growth, cell migration and invasion through its downstream target Akt3, E2F3 and c-Myb [34, 35], nevertheless, we found miR-424-3p could be up-regulated by baicalein. In addition, previous studies have demonstrated that baicalein is able to inhibit the proliferation, invasion and metastasis of HCC through inducing cell cycle arrest and apoptosis via several cancer-related signaling including MEK/ERK, JNK, mTOR, NF-κB etc [5, 6].…”
Section: Discussionmentioning
confidence: 69%
“…For example, miR-191, an oncogenic miRNA, was shown to be highly expressed in HCC and involved in cell proliferation, apoptosis and epithelial mesenchymal transition in HCC, and its hypomethylation has been proved to be associated with poor prognosis [32], interestingly, here we found miR-191 could be down-regulated by baicalein; miR-222-5p and miR-675 were reported to be up-regulated in HCC tumor tissues and positively associated with recurrence after resection [33], whereas our result showed that they were both down-regulated under baicalein treatment; miR-424-3p has been demonstrated to be down-regulated in HCC and suppresses tumor growth, cell migration and invasion through its downstream target Akt3, E2F3 and c-Myb [34, 35], nevertheless, we found miR-424-3p could be up-regulated by baicalein. In addition, previous studies have demonstrated that baicalein is able to inhibit the proliferation, invasion and metastasis of HCC through inducing cell cycle arrest and apoptosis via several cancer-related signaling including MEK/ERK, JNK, mTOR, NF-κB etc [5, 6].…”
Section: Discussionmentioning
confidence: 69%
“…MiRNAs play their roles through binding to their target mRNAs and inhibiting their protein expressions [3840]. In our study, we identified ROCK1 as a direct target of miR-300 in glioblastoma.…”
Section: Discussionmentioning
confidence: 75%
“…For instance, miR-125a, which is always significantly downregulated in HCC, inhibits the metastasis of tumor cells by targeting MMP11 and vascular endothelial growth factor A (VEGF-A) [89]. Similarly, miR-424, which is also down-regulated in HCC, suppresses tumor cell migration and invasion through its downstream target cMyb [90]. Other key signaling molecules that promote metastasis of HCC are targeted by miRNAs, including a disintegrin and metalloprotease 17 (ADAM17), metastasis suppressor 1 (MTSS1), type I collagen alpha2 (COL1A2), and other factors [91][92][93].…”
Section: Deregulated Mirnas In Invasion and Metastasismentioning
confidence: 99%